Pentraxin-3 as a marker of sepsis severity and predictor of mortality outcomes: A systematic review and meta-analysis. Issue 1 (January 2018) - Lee, Yee Ting; Gong, Mengqi; Chau, Alex; Wong, Wing Tak; Bazoukis, George; Wong, Sunny Hei; Lampropoulos, Konstantinos; Xia, Yunlong; Li, Guangping; Wong, Martin C.S.; Liu, Tong; Wu, William K.K.; et al.
Summary: Objectives: Pentraxin-3 (PTX-3) is a multi-functional pattern recognition molecule produced by various cell types of peripheral tissues in different infections. It is raised in sepsis, but its values in predicting disease severity or mortality outcomes have been controversial. Therefore, we conducted a systematic review and meta-analysis of these associations. Methods: PubMed and Embase were searched until July 18, 2017 for studies that evaluated the relationship between PTX-3 levels and disease severity or mortality in sepsis. Results: A total of 23 and 10 entries were retrieved from both databases, respectively, of which 16 studies were included in the final meta-analysis. A total of 3001 patients (56% male, mean age 63 ± 15 years; mean follow-up duration of 207 days) were analysed. PTX-3 was significantly higher in patients with more severe sepsis compared to those with less severe sepsis (standard mean difference = 18.5 ng/mL, standard error: 4.5 ng/mL, P < 0.0001) and higher in non-survivors compared to survivors (standard mean difference = 40.3 ng/mL, standard error: 6.8 ng/mL, P < 0.0001). Elevated PTX-3 levels significantly increased the risk of all-cause mortality (hazard ratio: 1.91, 95% CI: 1.53 to 2.46, P < 0.0001). Conclusions: PTX-3 significantly predicts disease severity and mortality in sepsis.